Exploration of the relationship between inertia enhancement and DC-link capacitance for grid-connected converters - Guo, Ke (2019)
Grid-connected converters (GCCs) are showing potential in providing virtual inertia and has attracted wide attention recently. For the virtual inertia emulated by GCCs, it is proportional with the DC-link capacitance, and thus, the DC-link capacitance can directly affect the dynamic performance for the GCC emulating inertia through modifying the inertia constant. However, the impacts of the DC-link capacitance have never been discussed in any literature before. Considering this issue, the influence of the DC-link capacitance on the dynamic performance for the GCC providing virtual inertia is analyzed in this paper. In addition to that, the selection approach of the DC-link capacitance is presented by tuning the system damping ratio within its optimal range. Simulations verify the correctness.